OpenStudy (anonymous):

|x+5|=|x+3|

4 years ago
OpenStudy (austinl):

x = -4

4 years ago
OpenStudy (dmezzullo):

@austinL Explain ur answer plz, Don't just give the answer.

4 years ago
OpenStudy (austinl):

(-4) + 5 = 1--> |1| = 1 (-4) + 3 = -1 --> |-1| = 1

4 years ago
OpenStudy (anonymous):

How? Where did the 4 come from

4 years ago
OpenStudy (tkhunny):

What's your plan? If x > -3, we have (x+5) = (x+3) - Doesn't look promising If x < -5, we have -(x+5) = -(x+3) - Doesn't look promising If -5 < x < -3, we have -(x+5) = (x+3) - Now THAT might lead to something.

4 years ago
OpenStudy (austinl):

This was simplistic problem. i was able to deduce that it was -4 because it made the equation correct.

4 years ago
OpenStudy (anonymous):

Thank u

4 years ago
OpenStudy (austinl):

No problemo :)

4 years ago